Cooling effect analysis on para-ortho hydrogen conversion coupled in vapor-cooled shield. (12th May 2023) - Meng, Chuiju; Qin, Xujin; Jiang, Wenbing; Pu, Limin; Liu, Wei; Huang, Yonghua
Abstract: The conversion process from parahydrogen to orthohydrogen accompanies an endothermic effect. Embedment of a para-ortho hydrogen converter into the thermal insulation could enhance the thermal protection of a liquid hydrogen storage tank. A physical model was proposed to simulate the heat transfer behavior of the insulation structure that integrates a polyurethane foam, a blanket of multilayer insulation, a vapor-cooled shield, and a para-ortho hydrogen converter. The effect of the para-ortho conversion process was considered. The model was validated by experimental data and then used to investigate how the para-ortho hydrogen conversion influences the temperature distribution inside the composite insulation. It was found that a single converter improves the cooling performance most effectively if it is placed at the middle length of the venting pipe mounted on the vapor-cooled shield. Either incorporating more converters or extending the length of the vapor-cooled shield pipes brings limited further improvement. The optimum position of the vapor-cooled shield inside the multilayer insulation moves towards the cold boundary in the presence of para-ortho conversion, compared to conventional vapor-cooled shield and multilayer insulation structures. A net heat flux reduction of over 10% could be achieved when the para-ortho conversion is located at the optimal position inside the vapor-cooled shield. Graphical abstract: Image 1 Highlights: Thermal insulation with para to ortho conversion (POC) for LH2 tanks is studied. Factors influencing POC cooling performance are analyzed. Vapor-cooled shield (VCS) temperature decreases in presence of POC. Optimum VCS position moves towards the cold boundary in presence of POC. Net heat flux reduces up to 10% for an insulation structure by introducing POC.